Profiling the impact of different tau species on glial cell biology - Arribas Gomez, Ines; Yan, Yan; Lilley, Meredith T.; Chen, Yunfei; Daughrity, Lillian M.; Moreno Arnas, Ana; Shi, Ji; Kachergus, Jennifer M.; Thompson, E. Aubrey; Jansen-West, Karen; Cook, Casey N. (Frontiers in Cell and Developmental Biology, 2025)
IntroductionTauopathies are a heterogeneous group of neurodegenerative disorders characterized by abnormal tau protein accumulation in neuronal and/or glial cells. Different pathogenic tau mutations result in distinct patterns of tau deposition, yet the differential effects of these tau species on glial cell biology are poorly understood. This study examines glial cell function in response to two distinct tau variants: P301L (promoting insoluble/fibrillar tau) and A152T (favoring soluble/oligomeric tau).MethodsWe used adeno-associated virus to express human tau containing either the P301L or A152T mutation and delivered to the brain by intracerebroventricular injection on postnatal day 0. At 3 months of age, we used the nCounter mouse glial profiling panel to measure expression of 770 genes involved in glial cell biology in the brain. Differential expression and pathway analysis, as well as cell type profiling were performed to assess how glial cell signatures in P301L-AAV and A152T-AAV mice differ in comparison to the control group (GFP-AAV injected mice).ResultsP301L-AAV and A152T-AAV mice exhibited both common and distinct changes in their glial gene expression profiles. P301L-AAV mice showed a pronounced microglial inflammatory response with upregulation of microglial activation markers (Clec7a, Cst7, Gpr84) and inflammatory mediators (Ccl3, Nlrp3). A152T-AAV mice demonstrated a more prominent astrocytic response with upregulation of astrocyte-specific genes (Gdpd2, Ggta1, Aqp4, Fbln5). In addition, only A152T-AAV mice exhibited coordinated impairment in glucose metabolism, mitochondrial function, calcium signaling, protein clearance, and increased apoptotic signaling.DiscussionOur findings reveal that different patterns of tau accumulation elicit fundamentally distinct glial responses. Insoluble tau deposition (P301L) primarily triggers microglial inflammatory pathways without substantial metabolic disruption, suggesting a direct response to tau fibrils. In contrast, soluble tau species (A152T) impact multiple cellular mechanisms simultaneously, including metabolic function, calcium homeostasis, and phagocytosis, potentially explaining the neuronal loss previously observed in this model. These distinct cellular signatures expand our understanding of how tau contributes to neurodegeneration and may inform more targeted therapeutic strategies based on predominant patterns of tau accumulation in different tauopathies.